Determination of antitumor properties of cyclophosphazene derivatives bearing chalcone-groups against PC-3 cell lines - Tekin, Suat; Koran, Kenan; Ozen, Furkan; Gorgulu, Ahmet Orhan; Sandal, Suleyman (Wiley-Blackwell, 2015)
[Abstract Not Available]